2002
DOI: 10.1038/sj.bmt.1703658
|View full text |Cite
|
Sign up to set email alerts
|

DPB1 disparities contribute to severe GVHD and reduced patient survival after unrelated donor bone marrow transplantation

Abstract: Summary:In order to evaluate the impact of HLA-DBP1 incompatibilities on the occurrence of acute graft-versus-host disease (GVHD) in unrelated hematopoietic cell transplantation, we studied 57 donor/recipient pairs characterized by their allelic identity for HLA-A, B, C, DRB1 and DQB1 and also for DRB3, 4, 5 loci and aimed to correlate DPB1 mismatches to already described risk factors for GVHD using multivariate Cox regression analysis. DPB1 identity between donor and recipient was observed in 24% and DPB1 com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 28 publications
2
34
0
Order By: Relevance
“…The HLA-DOA gene, and its adjacent region, is of interest for several reasons. Compared with one of its 3′ neighbors, HLA-DPB1, which is highly polymorphic, and can influence immunological outcomes in bone-marrow, corneal and renal transplantation, the HLA-DOA gene is relatively non-polymorphic, and inhibits class II antigen presentation in mature B-cells; but its role in organ transplantation is unknown (29)(30)(31)19,20). Our findings lead us to speculate that a missing exon transcript may produce a dysfunctional HLA-DOA gene product, which facilitates rejection by failing to inhibit antigen presentation by B-lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The HLA-DOA gene, and its adjacent region, is of interest for several reasons. Compared with one of its 3′ neighbors, HLA-DPB1, which is highly polymorphic, and can influence immunological outcomes in bone-marrow, corneal and renal transplantation, the HLA-DOA gene is relatively non-polymorphic, and inhibits class II antigen presentation in mature B-cells; but its role in organ transplantation is unknown (29)(30)(31)19,20). Our findings lead us to speculate that a missing exon transcript may produce a dysfunctional HLA-DOA gene product, which facilitates rejection by failing to inhibit antigen presentation by B-lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies initially failed to demonstrate a significant impact of HLA-DPB1 mismatches on the incidence of aGvHD. 18,19 In contrast, one early 20 and several more recent reports [21][22][23][24] showed that the incidence of severe aGvHD was increased in HLA-DPB1-mismatched transplantations. Two of these reports suggested a cumulative impact of the number of HLA-DPB1 mismatches on the incidence of aGvHD.…”
Section: Introductionmentioning
confidence: 97%
“…13 The results obtained from clinical transplantation studies concerning the impact of mismatching for different HLA alleles have led to the current standard that patient and donor are usually preferably matched for the HLA class II alleles HLA-DR and HLA-DQ in addition to the HLA class I molecules. 14,15 The role of HLA-DP as a transplantation antigen is less clear. Clinical reports on the impact of matching for HLA-DP on transplant outcome and GVHD often showed conflicting results.…”
Section: Introductionmentioning
confidence: 99%